A new indole alkaloid, antioxidant and antibacterial activities of crude extracts from Saccocalyx satureioides. Issue 11 (2nd June 2020) - Kherkhache, Hayat; Benabdelaziz, Imane; Silva, Artur M. S.; Lahrech, Mokhtar Boualem; Benalia, Mokhtar; Haba, Hamada
Abstract: The new acylated indole alkaloid glucoside indole-3-carboxylic acid-(6'- O -caffeoyl)-β-D-glucoside 1 has been isolated from the ethyl acetate (EtOAC) extract of Saccocalyx satureioides Coss. & Dur. (Lamiaceae) together with eight known secondary metabolites 2 -9 . Two indoles 2 and 3, five methylated flavone aglycones 4-8 and one monoterpene glucoside 9 were reported for the first time in the genus Saccocalyx. The structural elucidation of these compounds was accomplished by spectroscopic methods including 1 D ( 1 H and 13 C) and 2 D (COSY, HSQC and HMBC) NMR techniques, and mass spectrometry, and by comparison with literature data. Light petroleum, EtOAc, chloroform and n -butanol ( n -BuOH) extracts of S. Satureioides were screened for their antioxidant activity using DPPH radical scavenging and β-carotene bleaching methods. The antibacterial activity of these extracts indicates that n -BuOH and EtOAc extracts possess the strongest activity. Graphical Abstract: